Merefleksikan Kembali Toleransi Bagi Kebersamaan Yang Pluralistik Antar Manusia - Yustinus J.W. Yuniarto; Ambrosius Heri Krismawanto; Nerita Setiyaningtiyas (Jayapangus Press, 2023)
Tolerance is an important concept when society experiences disputes or conflicts of interest. Misuse of the word tolerance occurs when the word only means there is no conflict on the surface layer of people”s lives. In fact, the potential for conflict is like burning husks. Sowing the seeds of tolerance is not just aimed at eliminating differences or eliminating conflicts. Tolerance is the essence of the existence of society itself. This article will analyze the concept of tolerance and how to raise awareness that tolerance stems from a person”s self-concept in looking at those around him. The following article reviews the ideas behind the term tolerance. Tolerance has breadth and depth of meaning. This study employed qualitative method with literature research design. Data were analyzed with content analysis method. The study results show that tolerance grows as part of the human personality. When humans are able to embrace tolerance, there is a guarantee that the preservation of all differences and all kinds of conflicts can continue constructively. Both must exist for the sake of humanity. It is hoped that the meaning of the value of tolerance will not be manipulated by people who have evil intentions to justify their evil behavior and actions. Nor should the idea of tolerance be used by humble and simple people to hand over their rights to arrogant and greedy people. Tolerance should not benefit the evil one and harm those who live simply.